HARMONI DALAM PERBEDAAN: Strategi Pengelolaan Keragaman Beragama - Sefriyono Sefriyono (Universitas Islam Negeri Imam Bonjol Padang, 2014)
This study concentrates on a plurality society situates in the sub-district of South Padang, West Sumatra whereits people hold different religion, language, social statification and etnicity. Data is gathered from a variousrespondents who live in the area including heads of the subdistrict, civil servants, common people, religousleaders, aducators, and students. Interviews, observation and collecting documents are used in collecting datafrom the respondents. This study shows that the society has succesfully managed its plurality in gaining socialintegration and harmony. The finding also reveals that people widely acknowledge the nature of the pluralityin the society to which they are adhering to different religions; their aspirations are fairly represented in thepublic sphere; they received equal treatments from the local government in concerning with the matter of socialwalfare. However, it also shows that the minorities groups have not fully gained their right to have particularplace for ritual.